Pola Komunikasi Politik dalam Proses Perumusan Pembangunan Gedung PKL Berdasarkan Peraturan Daerah Kabupaten Garut Nomor 12 Tahun 2015 - Haelvyn Pratagrahana Putra; Yusa Djuyandi (Pencerah, 2023)
The policy enacted by the Garut local government under Regulation Number 12 of 2015, which pertains to the maintenance of order, cleanliness, and aesthetic appeal, as well as the construction of street vendor buildings 1 and 2, has been deemed ineffective in addressing the issues faced by street vendors in Garut. The persistence of street vendors in conducting sales activities within the red zone, despite the availability of designated facilities, is the underlying cause of this phenomenon. This suggests a lack of success in the process of formulating policies. This study aims to investigate the phases of policy formulation through the lens of political communication, drawing on Anderson and Sydney's theoretical framework of public policy. Specifically, the research will analyze the communication patterns that emerge during the formulation stage. The present investigation employs qualitative research methodologies, including literature reviews and observation techniques. The findings of the study indicate that the communication strategy employed in the development of this policy does not accurately reflect the requirements of the populace. The observed pattern can be attributed to the exclusion of street vendor unions from the formulation phase of the policy, with their involvement being limited to the implementation stage. This phenomenon engenders a deficiency in the perception of ownership of the policy among street vendors, thereby impeding their compliance and engendering a sense of disadvantage stemming from the policy's existence.